Islamic Republic of Mauritania : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2012)
Despite a relatively high GDP growth rate over the past decade (2000-10), economic growth in Mauritania has not been able to make a significant dent in poverty. Rapid and sustained poverty reduction requires inclusive growth that allows people to contribute to and benefit from expanding economic activity. Mauritania needs to make greater progress toward inclusive growth by enhancing the distributional impact of public spending and by improving the quality of pro-poor spending. The Executive Board recommends effective monetary policies to meet the challenges.